Frequency and characteristics of occupational injuries and infections in senior medical students: a 5-year retrospective study - Muhsin Güllü; Alpaslan Türkkan (Discover Public Health)
Abstract Background Workplaces present health and safety risks, especially for healthcare workers, such as medical students, who face a variety of hazards. Despite acquiring skills during medical school, medical faculty students, especially those engaged in patient-related practices, face increased injury risks due to factors such as lack of knowledge, insufficient practice, and high workload. This study aimed to determine the frequency and characteristics of occupational injuries and infections among senior medical students. Methods This descriptive cross-sectional study analyzed the occupational health and safety unit and hospital electronic records of needlestick and sharp injuries, mucosal exposure and occupational trauma injuries from January 1, 2019, to December 31, 2023. Data, including demographic details, injury specifics, and students’ post-injury attitudes, were collected from the records. Results In this period, 554 senior students experienced 666 injuries, with frequency rates ranging between 22.6% and 75.1% from 2019 to 2023. The majority (60.2%) were female, and injuries were most common in the Emergency Department (65.8%), predominantly affecting the hand/finger (86.2%). Of the 554 students, three were HbsAg positive, 13 were anti-HbS negative, two were anti-HCV positive, and one was anti-HIV positive. Given the possible window time, just 20.4% of the 554 students submitted control blood samples following injury. Conclusion The research revealed a significant prevalence of work-related injuries among senior medical students, particularly in departments with elevated risk levels such as the Emergency Department. These results emphasize the need for improved injury prevention training and awareness. Furthermore, it is emphasized that taking blood tests after the suitable window time is crucial in order to promptly diagnose and treat bloodborne disorders after an accident.